Eksistensi Kerajaan Bunga Bali di Alor pada Masa Pemerintahan Raja Baololong Kaay, 1840-1875 - Susilo Setyo Utomo; Malkisesdek Taneo; Mardhi Abiatar Letuna (Jurnal Sejarah Citra Lekha, 2021)
This article aims to reveal the economic, political and social conditions of the Bunga Bali Kingdom during the reign of King Baolong Kaay in 1840-1875, as well as to revealing his role in political diplomacy in the Lisbon Treaty which certainly had shown existence of the Bali Bunga Kingdom. This study focuses on the locus of the territorial area of the Bunga Bali Kingdom which is centered at Alor Besar. This study uses a historical approach by emphasizing historical facts. Data were obtained from literature or document studies, observations, field studies, and oral traditions. According to this study, there is an economic dependence of the community on the agricultural, livestock and fishery sectors, as well as the political situation. The Bunga Bali  Kingdom has 10 Adang villages, three Islamic villages, and seven Pura villages. This study also reveals the social relations of local communities that did not recognize the division of social classes. On the other hand, the emergence of King Baololong as a mediator in the Lisbon treaty in Sago (Solor) was an important turning point because it resulted in an agreement on the territorial division and recognition for the Portuguese and the Dutch. The territories of Kolana, Batulolong, Kui, and Mademang were given to the Dutch, while the island of Atauro was given to the Portuguese. Meanwhile, based in the participation in the Lisbon, it was a medium of achievement and pride for the community as well as to strengthen the ties of brotherhood and cooperation between Galiyau Watang Lema and Solor Watang Lema.